Pengaruh Pet Attachment Terhadap Psychological Well Being Pemilik Hewan Peliharaan Di Kota Gresik - Rizka Wahidah; Muhimmatul Hasanah; Setyani Alfinuha (Psikosains: Jurnal Penelitian dan Pemikiran Psikologi, 2023)
Keeping pets is a hobby for many people and having an attachment to pets is also considered beneficial for their owners. This study aims to determine the effect of Pet Attachment on Psychological Well Being. This research uses quantitative methods. Determination of the sample using incidental sampling technique, as many as 105 respondents. Research data were collected by distributing questionnaires on the Pet Attachment Questionnaire (PAQ) scale developed by Zilcha-Mano, Mikulincer dan Shaver (2011) and the Psychological Well Being scale developed by Ryff (1989). The analytical method used is simple linear regression analysis. The results of the analysis using a simple linear regression test get a sig value of 0.311, meaning that the significant value is more than > 0.05. So it can be concluded that there is no significant effect between Pet Attachment on the Psychological Well Being of pet owners in Gresik City.